Characteristics of Regular Pulse Bursts Generated From Lightning Discharges - Yanhui, Wang; Xiangpeng, Fan; Tuo, Wang; Yingchang, Min; Yali, Liu; Guo, Zhao (Frontiers in Environmental Science, 2021)
The waveforms of lightning discharges during a period of 15 minutes were assessed. Eighty-three percent of all lightning discharges contain particular waveforms called regular pulse bursts (RPBs), which have regular microsecond-scale electric or magnetic ﬁeld pulses. Most RPBs tend to occur in the middle and later stages of lightning discharges. Prior to or after RPBs, there is always a chaotic pulse period. The analysis indicated that RPBs are caused by a secondary discharge in the fractured old breakdown channel, similar to the dart-stepped leader in negative cloud-to-ground discharge (-CG). Four types of RPBs, namely, normal RPBs, back RPBs, symmetric RPBs, and reversal RPBs, were classified according to the evolution of the pulse amplitude, interval between neighboring pulses and pulse polarity. In addition, the difference between normal RPBs and back RPBs was considered to be caused by the distance between neighboring charge pockets and the magnitude of the charge in every charge pocket. The symmetric RPBs were considered to be caused by a discharge channel with a large central charge area. Reversal RPBs were considered to be caused by a bending channel or superposition of two or more RPBs. Some RPBs were mapped in three dimensions in a typical intracloud flash. The analysis showed that the developing velocity of RPBs ranged from approximately 1.2×106 m/s to 3.0×106 m/s, which is slightly less than that of the dart-stepped leader or dart leader process from previous studies. The step lengths marked by pulses ranged from approximately several meters to dozens of meters.